History, Status, Impacts, and Management of Invasive Black Spiny-tailed Iguanas (Ctenosaura similis) on Gasparilla Island, Florida. - Sean L. McKnight; Bryan M. Kluever; Parker Hall; Miguel A. Acevedo; Steve A. Johnson (EDIS, 2023)
This publication summarizes the history, status, and management of invasive black spiny-tailed iguanas (Ctenosaura similis) on Gasparilla Island, in southwest Florida. Our target audiences are residents and visitors of Gasparilla Island as well as naturalists interested in Florida’s diverse wildlife, especially introduced reptiles. Our specific goal is to increase knowledge and raise awareness about black spiny-tailed iguanas, their impacts, and the challenges of managing those impacts. More broadly, we aim to raise awareness about the many introduced and invasive reptiles in Florida and motivate people to take action to help prevent additional introductions of nonnative reptiles as well as support management efforts to curtail the spread of introduced reptiles in the Sunshine State. The information used to produce this publication was derived from published scientific articles, communications with colleagues, and our own research.